Usage WhatsApp in Improving Arabic Writing Skills Students at Higher Education University of Malaysia - Zulkifle, Syahmi Syahmi; Zakaria, Zarima Mohd (Institut Agama Islam Negeri Curup, 2024)
Application WhatsApp is one of the most popular communication tools nowadays. The use of WhatsApp is widely used in the field of education and human daily life. In addition, through previous studies, explained the difficulty of writing Arabic such as arranging sentences, appropriate terms and the correct method according to the correct Arabic grammar in the aspect of writing instead of in WhatsApp. To find out the level of students' writing, WhatsApp is used especially when it comes to writing. Therefore, this study focuses on exploring the level of WhatsApp usage in Arabic writing skills among Arabic language students at IPTA. The method used in this study uses a quantitative approach in the form of a questionnaire involving 126 students. Each response in the survey was analyzed using SPSS software. Each finding shows the level of WhatsApp application usage in social activities in daily life and the level of WhatsApp usage in learning at public universities. The results indicate a high usage level WhatsApp application usage in social activities in daily life and the level of WhatsApp students usage in learning at public universities with a min value of 4.00 above for most each aspect. The student need to optimize their use of WhatsApp in their learning activities so that their writing skills become more proficient and accurate in exploring the level of WhatsApp usage in Arabic writing especially by using it in daily activities and Stages of WhatsApp activities in learning at IPTA.